1999
DOI: 10.1139/z99-149
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and experience on the reproductive performance and prenatal expenditure of resources in female fallow deer (Dama dama)

Abstract: In this paper we tested whether prenatal expenditure of resources in fallow deer (Dama dama) is affected by the age and reproductive experience of mothers. The study was carried out on the wild fallow deer population in Doñana National Park in southwestern Spain. Between 1985 and 1996 a total of 60 different females were monitored by direct observation during the fawning season. The exact age of 22 of these females was known, and 59 fawns born of these females were captured. The mother's age had more influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…These younger females may be less likely to implant a fertilized egg or maintain a developing foetus. Yearling females also give birth later (average 11 days) and to lighter offspring with higher mortality rates [23], [24], [56]. In our study, the influence of male age and male dominance rank on the age of females they mated with was very weak.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These younger females may be less likely to implant a fertilized egg or maintain a developing foetus. Yearling females also give birth later (average 11 days) and to lighter offspring with higher mortality rates [23], [24], [56]. In our study, the influence of male age and male dominance rank on the age of females they mated with was very weak.…”
Section: Discussioncontrasting
confidence: 55%
“…Female fallow deer reach sexual maturity at 18 months and can reproduce until 23 years old [23] , [24] . Yearling females (one year old) are approximately 14% lighter than older females (mean: yearlings = 37 kg; adult females = 42 kg) and fecundity is strongly positively related to body weight in yearling females but not in older females [23] .…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Festa-Bianchet et al (1994), we found that most female mountain goats at Caw Ridge produced their first kid at 4-5 years old, 2-3 years later than other ungulates of similar body size (Ozoga & Verme 1986;Festa-Bianchet et al 1995;Byers 1997;San José et al 1999). In addition, primiparity was later at Caw Ridge than in introduced populations of mountain goats (Houston & Stevens 1988;Bailey 1991).…”
Section: Kid Productionsupporting
confidence: 77%
“…Significant differences between years are common [ 29 , 30 ]. Age, weight, and condition of the does, quantity and quality of feed, weather (temperature, humidity, wind, exposure to sun), and management (appropriate shelter and fawning area) are seen as important factors influencing perinatal mortality [ 31 ]. Essentially, nonviable fawns born at the right time of the year appear to be due to underweight or yearling mothers [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age, weight, and condition of the does, quantity and quality of feed, weather (temperature, humidity, wind, exposure to sun), and management (appropriate shelter and fawning area) are seen as important factors influencing perinatal mortality [ 31 ]. Essentially, nonviable fawns born at the right time of the year appear to be due to underweight or yearling mothers [ 31 33 ]. Furthermore, a low birth weight has been identified as a major cause of loss in newborn fallow and red deer [ 20 , 29 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%